(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
We consider New Keynesian DSGE model with Vietnamese data from January 2000 to April 2015. We study the impact of the preference shock, cost-push shock, technology shock and monetary policy shock to the movement in key macroeconomic variables such as the short-term nominal interest rate, the output gap, inflation, and especially output growth. Moreover, we evaluate how important the information from the DSGE model is by considering the ratio of artificial DSGE observations over actual observations. The comparison of the marginal likelihoods of the DSGE-VAR models with different sample sizes of the artificial data generated from the Ireland model provides the best-fitting value, which shows the information from the DSGE model is useful.